#Virtual Lexicality. The semantics of innovative prefixed verbal anglicisms in German. (October 2017) - Baeskow, Heike
Abstract : The increasing influence of the digital media affects not only the behaviour of Internet users, but also calls for constant lexical innovation. Since most of the IT-related vocabulary originated in English, it is a particular challenge to examine how individual lexical items from this domain are processed as loan words in a receptor language. In this article it will be shown that there is a tendency in present-day German to form verbs denoting the use of online services by means of analogy (e.g. googeln > facebooken, youtuben, whatsappen ) and that these verbs already participate in native derivational processes. Significantly, web-based searches performed for this study revealed that they occur in the context of the German inseparable prefixes er -, be -, ent -, ver - and zer - at least in computer-mediated communication. Given this behaviour on the one hand and the restricted use on the other, it is assumed here that these hybrid formations are pragmatically motivated. In particular, they allow Internet users to differentiate between real-world activities and corresponding activities simulated in the virtual world. Moreover, it will be argued that the prefixed verbal anglicisms activate slots in the paradigms of the grammaticalized prefixes, where they are paradigmatically related to genuinely native neighbours (e.g. ergoogeln, erfragen, erarbeiten ). In the course of the discussion, the analyses will be extended to include borrowed verbs like chatten, liken, or followen, which are also compatible with the prefixes under consideration.